Studi Hadis Tematik : Pendekatan Klasik dan Kontemporer - Sahrul Ulum; Muhammad Alif (STIKes Ibnu Sina Ajibarang, 2025)
This scientific work discusses the analysis of thematic hadith studies, which encompasses both traditional and contemporary methodologies, having a broad and multidimensional scope. The classical paradigm primarily emphasizes the affirmation of originality and the literal validity of hadith texts, while contemporary approaches promote a more contextual and critical interpretation by integrating various interdisciplinary techniques. Using a thematic framework allows for a more holistic understanding of hadith by systematically analyzing relevant texts within specific thematic categories. As a result, thematic hadith analysis goes beyond the examination of texts and chains of narration (sanad), incorporating considerations of socio-cultural context and the development of scientific knowledge. This comprehensive approach aims to enhance the relevance and application of hadith studies in modern Muslim society.